Strategi Pengembangan SDM Berbasis Kepemimpinan Transformatif dan Pelatihan Berkelanjutan dalam Meningkatkan Kinerja Guru - Syahrial, Syahrial; Surya Adri; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Human resource development (HRD) is a strategic element in improving teacher performance and educational quality. This article aims to analyse effective HRD strategies within educational institutions, particularly through training management, transformational leadership, and performance management based on affective commitment. This study employs a qualitative descriptive approach using a library research method, drawing upon various secondary data sources including scientific journals, textbooks, research reports, and official institutional documents published between 2020 and 2025. The data were analysed using thematic content analysis through four stages: data reduction, thematic coding, interpretative analysis, and conclusion drawing. The results indicate that effective HRD strategies include : 1) continuous professional development and teacher training to enhance competence and motivation, 2) transformational and participatory school leadership that strengthens collaborative culture, and 3) performance management systems emphasizing teacher well-being and affective commitment. The findings suggest that HRD strategies focusing on motivational, psychological, and structural aspects can sustainably improve teaching effectiveness and educational quality.